Theological Interpretation of the Ke’o rado Ritual for the Cultivation of the Christian Faith Among the Ngadhanese, Flores, Eastern Indonesia - Lina, Paskalis; Dose, Fransikus; Dhogo, Petrus Cristologus (Asosiasi Ahli Filsafat Keilahian Indonesia, 2023)
The ke'o rado ritual is a rite of reconciliation and purification for those who have had a tragic death (mata golo) in the Ngadhanesse, Flores, Eastern Indonesia. The primary purpose of this article is to interpret the meaning of the ke'o rado ritual and its theological implications. This paper is a qualitative descriptive study and participatory observation using a literature review and key informant interviews. The study found no official confirmation from the Catholic Church authorities in Ngada that ke'o rado contradicts Christian doctrine. However, some Ngada people consider that the ritual is contrary to the teachings of the Christian faith regarding salvation in Christ and thus should be abandoned. In contrast, this paper concludes that the ke'o rado ritual must be observed since it has theological significance and can be brought into dialogue with the teachings of the Christian faith.